2020
DOI: 10.1038/s41598-020-60540-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolome analysis reveals novel connections between maternal fecal metabolome and the neonatal blood metabolome in women with gestational diabetes mellitus

Abstract: Gestational Diabetes Mellitus (GDM), which is correlated with changes in the gut microbiota, is a risk factor for neonatal inborn errors of metabolism (ieMs). Maternal hyperglycemia exerts epigenetic effects on genes that encode IEM-associated enzymes, resulting in changes in the neonatal blood metabolome. However, the relationship between maternal gut microbiota and the neonatal blood metabolome remains poorly understood. this study aimed at understanding the connections between maternal gut microbiota and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Previously, using untargeted metabolic profiling, Zhao et al 21 found that the overall fecal metabolomic signature of GDM was distinct from that of HC. They also found that fecal amino acid levels (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using untargeted metabolic profiling, Zhao et al 21 found that the overall fecal metabolomic signature of GDM was distinct from that of HC. They also found that fecal amino acid levels (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Systems biology inaugurated a new era of biological and biomedical research, which is different from the traditional one-gene-at-a-time approach, which discovers detailed molecular functions of individual genes or proteins[ 13 ]. Systems biology includes genomics, transcriptomics, proteomics, and metabolomics to comprehensively research the changes in biological systems under physiological and pathological conditions[ 14 ]. Among them, the concept of metabolomics was first put forward by Nicholson et al [ 15 ] in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, many risk factors for GDM have been identified, including advanced maternal age, family history of diabetes, prepregnancy overweight and obesity, and genetic components[ 14 ]. However, the etiology and pathogenesis of GDM are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, it is now suspected that microbiota metabolites play a main part in maternal epigenetic regulation of GDM and in programming the child's metabolite profile. In the publication by Zhao et al [106], the relationship between maternal faecal matabolome and neonatal blood metabolome was investigated. The authors observed a negative prevalence in the presence of 4 different fecal metabolites in mothers with GDM compared to the control group -lysine, putrescine, guanidinoacetate and hexadecanedioate.…”
Section: The Role Of Microbiota In Gdm Developmentmentioning
confidence: 99%